Studi Hukum: Optimalisasi Peran Jaksa Jaga Desa Dalam Mencegah Korupsi Dana Desa - Yaoma Tertibi; Arum Ayu Lestari (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2026)
This research aims to explore the role of “Jaksa Jaga Desa” (Village Supervising Prosecutors) in the effort to prevent village fund corruption. Corruption and abuse of authority in the management of village funds are serious problems that impact community development. Through a qualitative approach, this study identifies the strategies and best practices implemented by the